Mumbit Hilal Sebagai Tempat Awal Berkembangnya Peradaban Islam - Arfah Ibrahim (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The existence of Islamic civilization today cannot be separated from the history of world civilization which is found in Fertile Crescent which is the center of the oldest civilization in the world. The fertile hilal region is a crescent-shaped area containing wet and fertile soil between the arid or semi-arid lands of West Asia, and between the three rivers important for humans: Euphrates, Nile and Tigris. This area is called the birthday of civilization because there was a lot of development of early human civilization and it became the target of Muslims to be able to control the area until finally in the VII century AD, Muslims were able to enter and control the fertile hilal area and became the beginning history of the development of Islamic civilization in the world. that we know today.